2006
DOI: 10.1021/ie051407l
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Conversion of CO2 to Methanol Catalyzed by Three Dehydrogenases Co-encapsulated in an Alginate−Silica (ALG−SiO2) Hybrid Gel

Abstract: In this study, the conversion of carbon dioxide to methanol was realized through a novel biochemical approach that was catalyzed by three dehydrogenases:  formate dehydrogenase (FateDH), formaldehyde dehydrogenase (FaldDH), and alcohol dehydrogenase (ADH). The dehydrogenases were encapsulated in an alginate−silica (ALG−SiO2) hybrid gel, which was prepared through in situ growth of the silica precursor within an alginate solution, which was followed by Ca2+ cross-linking. Methanol yields that were catalyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 35 publications
2
81
0
3
Order By: Relevance
“…[2][3][4][5] In this enzyme cascade, one molecule of methanol is produced at the cost of three equivalents of NADH. It is environmentally beneficial to convert CO 2 into useful biofuel by enzymatic reactions, but the high cost of stoichiometric NADH consumption makes this process impractical.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] In this enzyme cascade, one molecule of methanol is produced at the cost of three equivalents of NADH. It is environmentally beneficial to convert CO 2 into useful biofuel by enzymatic reactions, but the high cost of stoichiometric NADH consumption makes this process impractical.…”
mentioning
confidence: 99%
“…1 It was reported that the combination of three NAD + -dependent dehydrogenases (formate dehydrogenase, formaldehyde dehydrogenase and alcohol dehydrogenase) is capable of generating methanol from CO 2 by reversing the original enzymatic reaction direction. [2][3][4][5] In this enzyme cascade, one molecule of methanol is produced at the cost of three equivalents of NADH. It is environmentally beneficial to convert CO 2 into useful biofuel by enzymatic reactions, but the high cost of stoichiometric NADH consumption makes this process impractical.…”
mentioning
confidence: 99%
“…In addition, different immobilization strategies have also been described in the literature, such as enzyme encapsulation (Xu et al 2006), but showing lower yields in comparison with our methodology. Encapsulation of dehydrogenase enzymes in silica matrix exhibited methanol yields between 16.8% and 43.8%.…”
Section: Merging the Immobilized Enzymes In Catalysismentioning
confidence: 94%
“…To overcome these problems, several modifications to the sol-gel technique were proposed to improve the stability of the biological activity [36][37][38][39][40]. The dehydrogenases encapsulated in the alginate-silicate composite showed high initial enzyme activity retention, and significantly improved stability during storage and reuse [36]. These enzymes can be also immobilized in flat-sheet polymeric membranes simultaneously or separately by simple pressure-driven filtration (i.e., by directing membrane fouling formation), without any addition of organic solvent [41].…”
Section: Conversion Of Co2 To Formic Acid/formatementioning
confidence: 99%
“…To provide the possibility for practical application, a hybrid enzymatic/photocatalytic approach for efficient converting CO2 into methanol was recently proposed [35]. The proposed approach includes two processes: the enzymatic transformation of CO2 to However, this process still has several problems such as cosolvents and catalysts are in the sol-gel process due to low water solubility and reactivity of the silica precursor, and the alcohol liberated from hydrolysis, cosolvents, and catalysts are deleterious to bioactivity [36]. To overcome these problems, several modifications to the sol-gel technique were proposed to improve the stability of the biological activity [36][37][38][39][40].…”
Section: Conversion Of Co2 To Methanolmentioning
confidence: 99%